La nutrición y dietética infantil y su incidencia en el desarrollo cognitivo en niños y niñas menores de 5 años del C.I.B.V las Gardénias, cantòn Pujilí, provincia de Cotopaxi, durante el período 2013-2014 - Mata Ayabaca, Elizabeth Magaly (2015)
The investigation on the theme: “Children Nutrition and Diet and its incidence in the cognitive development of under five year old boys and girls of the Gardénias C.I.B.V”. Aimed at determining the influence of Children Nutrition and Dieting in the Cognitive Development of under five year old boys and girls; themes on Nutrition and Dieting were scientifically analyzed which with it will be possible to get to know nutritious food which help their growth, and at the same time better eating habits will be generated, during the research process, field instruments were applied form which real information on the investigated problem was obtained, where it was evident that in the institution, teachers do not know about the topic of Children Dieting and its incidence in the cognitive area of the infant; hence it was considered that elaborating a workshop that collect....